2022
DOI: 10.3390/ijerph19063556
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Determinants of Nascent Social Entrepreneurial Behaviour

Abstract: Following the emergence of social, environmental, and public health issues, this study analysed the determinants of nascent social entrepreneurial behaviour. This research investigated the effects of empathy and prior experience with social problems on nascent social entrepreneurial behaviour through social entrepreneurial self-efficacy, outcome expectations of social entrepreneurship, and perceived social support. Through utilising the quantitative survey method, this study gathered a total of 560 valid respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
0
7
0
1
Order By: Relevance
“…In the present study, nearly 1000 respondents were recruited. Although women comprised 55.1% of the sample, a proportion higher than that in the Taiwanese population, this was considered acceptable because other research has reported samples with similar proportions of women (Ip et al, 2022;. The demographics of the valid respondents are reported in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, nearly 1000 respondents were recruited. Although women comprised 55.1% of the sample, a proportion higher than that in the Taiwanese population, this was considered acceptable because other research has reported samples with similar proportions of women (Ip et al, 2022;. The demographics of the valid respondents are reported in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…That is also a reason why a body of prior studies have only focused on investigating the nature and determinants of social entrepreneurial intention (Hockerts, 2017;Hockerts, 2018;Paramita et al, 2022;Zaremohzzabieh et al, 2019;Chandra et al, 2021b). Nevertheless, social entrepreneurial intention does not always translate into social start-up behaviors (Ip et al, 2022;Akter et al, 2020), and scholars have identified an intention-behavior gap in social Applying the stimulusorganismresponse theory entrepreneurship (Rey-Martí et al, 2016;Muldoon et al, 2022). In other words, if would-be social entrepreneurs do not carry out social start-up activities and projects, although they have high initial intentions to become social entrepreneurs, then their fruitful social entrepreneurship processes are not actualized (Ip et al, 2022).…”
Section: Behavioral Responses: the Intention-behavior Link In Social ...mentioning
confidence: 99%
“…Nevertheless, social entrepreneurial intention does not always translate into social start-up behaviors (Ip et al, 2022;Akter et al, 2020), and scholars have identified an intention-behavior gap in social Applying the stimulusorganismresponse theory entrepreneurship (Rey-Martí et al, 2016;Muldoon et al, 2022). In other words, if would-be social entrepreneurs do not carry out social start-up activities and projects, although they have high initial intentions to become social entrepreneurs, then their fruitful social entrepreneurship processes are not actualized (Ip et al, 2022). It is, thus, important to advance our understanding of the so-called intention-behavior gap in social entrepreneurship (Thelken and de Jong, 2020;Muldoon et al, 2022).…”
Section: Behavioral Responses: the Intention-behavior Link In Social ...mentioning
confidence: 99%
“…Ip et al. (2022) stated that the effects of prior experience and social entrepreneurial SE are still consistent predictors of behavior. The authors argued that prior experience boosts venture emergence through opportunity confidence, as experience leads to stronger opportunity appraisal abilities and more justifiable option feasibility judgments.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Previous experience in business ownership or management increases the likelihood of becoming an entrepreneur or of developing EIs (Khan et al, 2019). Ip et al (2022)…”
Section: 37mentioning
confidence: 99%